2016
DOI: 10.5761/atcs.oa.15-00239
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carperitide in Hemodialysis Patients Undergoing Cardiac Surgery

Abstract: Purpose: Recently, performance of cardiac surgery in hemodialysis patients has increased, but the mortality rate is high. Methods: We retrospectively examined the early and long-term outcomes in 128 dialysis patients who underwent cardiac surgery with or without carperitide infusion and were followed for 2 years. Sixty-three patients received carperitide infusion during surgery and 65 patients did not. Results: The hospital mortality rate was 1.6% in the carperitide group and 12.3% in the non-carperitide group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Considering the sample sizes in these previous studies (65 and 108) are relatively small and their enrolled patients were restricted on hemodialysis patients, further study with larger sample size concerning CAPD patients is needed. In our study, we enrolled 198 ESRD patients undergoing CAPD (a relatively larger sample size), and we found that MACCE incidence at 1 year, 2 year, 3 year and 4 year was 2.5, 6.1, 9.1 and 13.1% respectively, and the mean MACCE-free survival was 45.2 (95% CI 44.0-46.4) months in CAPD patients, these results might be different compared to those previous studies, and the reasons might be: (1) MACCE incidence of our study was lower than that in one previous study, which might be due to the lower age as well as shorter dialysis duration of enrolled patients in our study [15]; (2) MACCE-free survival in our study was numerically shorter than another previous study, which might be due to the decreased follow-up duration of our study compared to the previous study [16].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Considering the sample sizes in these previous studies (65 and 108) are relatively small and their enrolled patients were restricted on hemodialysis patients, further study with larger sample size concerning CAPD patients is needed. In our study, we enrolled 198 ESRD patients undergoing CAPD (a relatively larger sample size), and we found that MACCE incidence at 1 year, 2 year, 3 year and 4 year was 2.5, 6.1, 9.1 and 13.1% respectively, and the mean MACCE-free survival was 45.2 (95% CI 44.0-46.4) months in CAPD patients, these results might be different compared to those previous studies, and the reasons might be: (1) MACCE incidence of our study was lower than that in one previous study, which might be due to the lower age as well as shorter dialysis duration of enrolled patients in our study [15]; (2) MACCE-free survival in our study was numerically shorter than another previous study, which might be due to the decreased follow-up duration of our study compared to the previous study [16].…”
Section: Discussioncontrasting
confidence: 90%
“…In this study, we observed that: (1) MACCE incidence at 1 year, 2 year, 3 year and 4 year was 2.5, 6.1, 9.1 and 13.1% respectively in CAPD patients, and mean MACCE-free [15,16]. For instance, a study enrolling 65 hemodialysis patients discovers a 2-year MACCE incidence of 32.3%, and another study enrolling 108 hemodialysis patients shows a median cardiovascular disease-free survival of 7.63 years (95% CI 7.06-8.21 years) [15,16]. Considering the sample sizes in these previous studies (65 and 108) are relatively small and their enrolled patients were restricted on hemodialysis patients, further study with larger sample size concerning CAPD patients is needed.…”
Section: Discussionmentioning
confidence: 62%